PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI BIRO PERJALANAN ISKANDARIA TOUR AND TRAVEL TANGERANG, BANTEN - , RICO FERNANDO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to understand about whether the services quality consisting of tangibles, reliability, responsiveness, assurance and empathy have significant effect to customerâs satisfaction in the travel bureau of Iskandaria Tour and Travel. The research is done by analyzing the service quality and inhabiting factor of the company. The population of this research is all customers in Iskandaria Tour and Travel who had been serviced by this company based on sale report data on January 2014. The quantity of the sample taken is 64 person and the sample determination technique which is used is non-probability sampling with purposive sampling approach. Purposive sampling is a sample determination technique based on the importance of researcher and their criteria were determined before. The customers who had six or more transactions were selected. Based on the result of statistical processing data using descriptive analyzing technique, it can be concluded that the services quality of the company is good enough. It is proved that 20 out of 22 questions distributed had the responds of agree and very agree above 50 %. However, there are still weakness in service delivery that are responsiveness and assurance dimension. The percentage of agree and very agree responds is below 50%. This included the speed to pick up customerâs telephone and also the guarantee of service accuracy. Furthermore based on linear regression analysis of one independent variable, the result shows that for each variable of the services quality and customers satisfaction have a sig point below 0,05 and it can be concluded that the services quality has significant effect to customer satisfaction.